Is the ‘Brainified’ Body a New Paradigm Candidate in Cognitive Science? Review of Joseph E. LeDoux, The Four Realms of Existence: A New Conception of the Human Being - Janicka, Joanna (Folia Philosophica, 2024)
The review discusses the concept of the human being proposed by American neuroscientist Joseph LeDoux in his book The Four Realms of Existence. LeDoux presents a vision of the human as a biologically constituted entity organized into four realms of existence that are both hierarchically structured and functionally parallel. The text summarizes the book’s content, highlighting its central themes and the innovative nature of the proposed model. The review aims to introduce LeDoux’s approach to prospective readers and encourage further reflection on its application within philosophy and cognitive science.